PEMBANGUNAN JARINGAN HOTSPOT SERVER DI DPM-PTSP PEKANBARU - Hutabarat, Sakti; Marpaung, Noveri Lysbetti; Siregar, Vivi Devina (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2023)
Agency of Asset Cultivation and One Door Integrated Service of Pekanbaru City is an organizer of One Door Integrated Service to handle various businesses of Government in city area. To enhance the quality of public service, so Government of Pekanbaru City forms region set, such as internet media as a main necessity in performing each someone’s work. Hotspot is a wireless internet network that can be accessed by all electronic sets, like as Personal Computer (PC), laptop, tablet and cellular phone. Hotspot also can be used in supporting daily activities to send data packet in certain amount through those electronic sets. Aim of this service is to build up Hotspot Server Networks Agency of Asset Cultivation and One Door Integrated Service of Pekanbaru City to improve public service in the framework to fulfill every body’s basic to conduct every person’s job. Method of this service is a series of activities such as Survey, Interview and Designing of Hotspot Server Network. This service succeed well. The result of this service shows that Bandwidth used for Uploding File are 0.35 Mbps and 0.29 Mbps for Downloading File.